2013
DOI: 10.1682/jrrd.2012.08.0135
|View full text |Cite
|
Sign up to set email alerts
|

Vibrotactile evaluation: Osseointegrated versus socket-suspended transfemoral prostheses

Abstract: Abstract-This study investigated detection thresholds of vibrometric stimuli in patients with transfemoral amputation supplied with osseointegrated (OI) and socket-suspended prostheses. It included 17 patients tested preoperatively with socket-suspended prostheses and after 2 yr with OI prostheses and a control group (n = 17) using socket-suspended prostheses, evaluated once. Assessments on the prosthetic and intact feet were conducted at six frequencies (8,16,32, 64, 125, and 250 Hz). Furthermore, measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 40 publications
0
40
0
Order By: Relevance
“…An advantage of direct attachment to the bone, regardless of the used BAP method, is that the patient has a better ability to detect vibrotactile and pressure stimuli of the prosthetic limb compared to socket prosthesis users [22, 37, 38]. These stimuli are also known as osseoperception.…”
Section: Introductionmentioning
confidence: 99%
“…An advantage of direct attachment to the bone, regardless of the used BAP method, is that the patient has a better ability to detect vibrotactile and pressure stimuli of the prosthetic limb compared to socket prosthesis users [22, 37, 38]. These stimuli are also known as osseoperception.…”
Section: Introductionmentioning
confidence: 99%
“…A further study found a similar result using vibration, but additionally found that detection thresholds in osseointegrated prostheses were better for higher frequencies ( 4100 Hz) (Häggström et al, 2013). Clinical observations have also found that patients can feel and judge mechanical loadings through osseointegrated prosthetics (Häggström et al, 2013).…”
Section: Towards a Promising "Sensory" Prosthesismentioning
confidence: 75%
“…Although the thresholds for detection were increased for both types of prosthesis, the osseointegrated prosthesis gave better detection thresholds than the socket-anchored prosthesis (Jacobs et al, 2000). A further study found a similar result using vibration, but additionally found that detection thresholds in osseointegrated prostheses were better for higher frequencies ( 4100 Hz) (Häggström et al, 2013). Clinical observations have also found that patients can feel and judge mechanical loadings through osseointegrated prosthetics (Häggström et al, 2013).…”
Section: Towards a Promising "Sensory" Prosthesismentioning
confidence: 86%
“…Cadence, duration of the gait cycle, and duration of the support phase of BAP users are also more similar to those of able-bodied persons than of SP users (Frossard et al, 2010b). A further advantage of BAP is the improved sensory feedback, known as osseoperception, resulting from the direct link between the prosthesis and skeletal system (Aschoff, Clausen, Tsoumpris, and Hoffmeister, 2011;Branemark, Branemark, Rydevik, and Myers, 2001;Haggstrom, Hagberg, Rydevik, and Branemark, 2013;Sullivan, Uden, Robinson, and Sooriakumaran, 2003). OPRA rehabilitation has been extensively described, but there are few descriptions of rehabilitation for patients with EEFP in the peerreviewed literature (Aschoff, Clausen, Tsoumpris, and Hoffmeister, 2011;Hagberg and Branemark, 2009;Van de Meent, Hopman, and Frolke, 2013).…”
Section: Introductionmentioning
confidence: 98%